Keterpaduan Maria dan Gereja dalam Sejarah Keselamatan Menurut Lumen Gentium dan Redemptoris Mater (Pusat Riset dan Inovasi Nasional, 2026)
This theological research explores Mary’s essential role in the narrative of salvation and her deep connection with the Church, as outlined in key Catholic documents like Lumen Gentium and Redemptoris Mater. Using a qualitative approach that combines descriptive and analytical methods, the study reviews Church teachings, Scripture, and theological literature. It highlights Mary’s pivotal status as Mother of God (Theotokos) a title affirmed by the Council of Ephesus in 431 CE, which underscores both Christ’s divinity and Mary’s unique participation in God’s redemptive plan. The study traces the theological roots of this title through biblical texts, portraying Mary as the chosen vessel through whom the Word became incarnate. It examines how Old Testament prophecies about Mary are fulfilled in New Testament events, especially in the Annunciation and Elizabeth’s greeting of Mary as “the mother of my Lord.” The research also delves into Mary’s bond with the Church, focusing on her recognition as Mother of the Church by Pope Paul VI during the Second Vatican Council. Mary is presented as the ideal disciple, embodying unwavering faith, obedience, and humility in her acceptance of God’s will. Her presence at key moments, from the Incarnation to Pentecost, positions her as both a member and a model of the Church. Ultimately, the study concludes that Mary’s unity with the Church is reflected in her dual role as Mother of Christ and spiritual mother to all believers, offering a profound example of Christian virtues and guiding the faithful in their collective journey toward salvation.